Linkage of the potent leukemogenic activity of Meis1 to cell-cycle entry and transcriptional regulation of cyclin D3 - Argiropoulos, B.; Yung, E.; Xiang, P.; Lo, C.Y.; Kuchenbauer, F.; Palmqvist, L.; Reindl, C.; Heuser, M.; Sekulovic, S.; Rosten, P.; Muranyi, A.; Goh, Siew-Lee; et al. (2010)
MEIS1 is a three-amino acid loop extension class homeodomain-containing homeobox (HOX) cofactor that plays key roles in normal hematopoiesis and leukemogenesis. Expression of Meis1 is ratelimiting in MLL-associated leukemias and potently interacts with Hox and NUP98-HOX genes in leukemic transformation to promote self-renewal and proliferation of hematopoietic progenitors. The oncogenicity of MEIS1 has been linked to its transcriptional activation properties. To further reveal the pathways triggered by Meis1, we assessed the function of a novel engineered fusion form of Meis1, M33-MEIS1, designed to confer transcriptional repression to Meis1 target genes that are otherwise up-regulated in normal and malignant hematopoiesis. Retroviral overexpression of M33-Meis1 resulted in the rapid and complete eradication of M33-Meis1-transduced normal and leukemic cells in vivo. Cell-cycle analysis showed that M33-Meis1 impeded the progression of cells from G(1)-to-S phase, which correlated with significant reduction of cyclin D3 levels and the inhibition of retinoblastoma (pRb) hyperphosphorylation. We identified cyclin D3 as a direct downstream target of MEIS1 and M33-MEIS1 and showed that the G(1)-phase accumulation and growth suppression induced by M33-Meis1 was partially relieved by overexpression of cyclin D3. This study provides strong evidence linking the growth-promoting activities of Meis1 to the cyclin D-pRb cell-cycle control pathway. (Blood. 2010; 115(20): 4071-4082)